Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Individualization Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Nurjanna Amini; Zulfah; Astuti; Molli Wahyuni; Zulhendri (Pendidikan Matematika FKIP Universitas Mataram, 2026)
The mathematical problem-solving ability of grade VIII students at SMPN Bangkinang is still low. This is evident from the average daily test scores, which remain below the Minimum Completeness Criteria of 70. This study aims to analyze the effect of using the Team Assisted Individualization (TAI) learning model on the mathematical problem-solving ability of grade VIII students at SMPN 1 Bangkinang. This research employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of two classes: an experimental class that implemented the TAI learning model and a control class that used conventional learning. The research instruments included a mathematical problem-solving test and observation sheets. The results of this study indicate that there is a difference in mathematical problem-solving ability between students who used the cooperative learning model type Team Assisted Individualization (TAI) and students who used conventional learning. This was proven by the Mann-Whitney U test on posttest data, in which the experimental class had an average score of 33.63, while the control class only scored 15.38. The significance value of 0.020 < 0.05 indicates that the difference is statistically significant. The effect of the cooperative learning model type TAI on problem-solving ability is categorized as very high. This is evidenced by the effect size calculation result of 1.3020, which, according to the effect size interpretation criteria, falls into the very high category. Thus, the implementation of the TAI model has a strong effect on improving students’ ability to understand problems, design solution strategies, and evaluate answers systematically.